Bakhtin and the actor (with constant reference to Shakespeare). - Emerson, Caryl (Studies in East European Thought, 2015)
The Bakhtin we know best is something of a lyricophobe and theatrophobe. This is surprising, since he loves the act of looking. His scenarios rely on visualized, collaborative communion. He cares deeply about embodiment. Does he care about the tasks that confront the actor? Not the improvising clown of carnival (carnival is theater only in the broad sense of performance art), but the trained artist who performs a play script on stage? In discussing these questions, this essay draws on two suggestive places in Bakhtin's writing where he addresses the actor's art. One is from the mid-1920s; the other (1944), is on Shakespearean tragedy. If Bakhtin has a theatrical imagination, it will be found here. His grasp of an actor 'living in' to a role and his comments on the evolution of the European stage cast his better-known ideas of dialogue, comedy, seriousness and the sacred into unexpected perspective.